ANALISIS STRATEGI DIFERENSIASI DALAM PELAYANAN BEAUTY SPA & SPA BABY TERHADAP KEUNGGULAN BERSAING DI RSIA ERIA BUNDA PEKANBARU - LPPM Al-Insyirah (STIKes Al-Insyirah Pekanbaru, 2016)
Beauty Spa & Spa baby is a service which is taken into account by RSIA Eria Bunda Pekanbaru to cope with the competition among the hospitals.Based on preliminary observations research, mother and child hospital Pekanbaru having services Beauty Spa & Spa baby Who have not owned by another hospital so that it can be renders it a strategy differentiation compete for excellence. This research aims to know the analysis of the strategy of product differentiation, service, personnel, channel and image in the serviceBeauty Spa & Spa babyAgainst excellence compete in mother and child hospital pekanbaru Years 2015. A method of research with the design descriptive qualitative research carried out mother and child hospital Pekanbaruapril 2015. A subject in research is the director, marketing staff, the head of finance, the head of the room and executive services Beauty Spa & Spa Baby, and patients and visitors.Data collection was done in the in-depth interviews with the informants and by doing observation. The results of research product differentiation among other Day spa product to the public and mainstay product namely spa services for mother in the aftermath of childbirth and babies.differentiation of services among othersSpa treatments do directly into the room without lowering the patient to patient spa room.Diferentiation of personnel among others Expert fisioteraphy, and skilled in the fields of beauty.Differentiation channel for currently serving patients/visitors in hospital.Differentiation image among othersThe product services can be enjoyed every patients and visitors in rsia eria mother , and the price package baby spa affordable. The conclusion of this study is differentiation strategy service Beauty Spa & Spa baby inmother and child hospital Pekanbaru yaers 2015 has been good enough.Then suggested to the hospital to improve the product of different services with competitors, designing distribution channels and improve promotion to patients and visitors of more aware of the excellence of these services.